Issue Information. Issue 1 (4th March 2020) - Unknown
Abstract : Cover : In Weeks and Wells (https://doi.org/10.1002/cpch.79, Application of subtiligase and specificity variants for N‐terminal modification. (A ) Subtiligase‐catalyzed modification of purified protein N termini. (B ) Workflow for subtiligase‐catalyzed cellular N terminomics. Abu, aminobutyric acid.